Cannabinoid WIN55,212-2 reprograms monocytes and macrophages to inhibit LPS-induced inflammation - Pérez-Diego, Mario; Angelina, Alba; Martín-Cruz, Leticia; de la Rocha-Muñoz, Andrés; Maldonado, Angel; Sevilla-Ortega, Carmen; Palomares, Oscar (Frontiers in Immunology, 2023)
Chronic or uncontrolled activation of myeloid cells including monocytes, macrophages and dendritic cells (DCs) is a hallmark of immune-mediated inflammatory disorders. There is an urgent need for the development of novel drugs with the capacity to impair innate immune cell overactivation under inflammatory conditions. Compelling evidence pointed out cannabinoids as potential therapeutic tools with anti-inflammatory and immunomodulatory capacity. WIN55,212-2, a non-selective synthetic cannabinoid agonist, displays protective effects in several inflammatory conditions by mechanisms partially depending on the generation of tolerogenic DCs able to induce functional regulatory T cells (Tregs). However, its immunomodulatory capacity on other myeloid cells such as monocytes and macrophages remains incompletely understood. Herein, we show for the first time that the differentiation of human monocyte-derived DCs (hmoDCs) in the presence of WIN55,212-2 generates tolerogenic DCs (WIN-hmoDCs) that are less responsive to LPS stimulation and able to prime functional Tregs. WIN55,212-2 also impairs the pro-inflammatory polarization of human macrophages by inhibiting cytokine production, inflammasome activation and rescuing macrophages from pyroptotic cell death. Mechanistically, WIN55,212-2 induced a metabolic and epigenetic shift in macrophages by decreasing LPS-induced mTORC1 signaling, commitment to glycolysis and active histone marks in pro-inflammatory cytokine promoters. We confirmed these data in ex vivo LPS-stimulated peritoneal macrophages (PMΦs), which were also supported by the in vivo anti-inflammatory capacity of WIN55,212-2 in a LPS-induced sepsis mouse model. Overall, we shed light into the molecular mechanisms by which cannabinoids exert anti-inflammatory properties in myeloid cells, which might well contribute to the future rational design of novel therapeutic strategies for inflammatory disorders.